2019
DOI: 10.3758/s13414-019-01723-6
|View full text |Cite
|
Sign up to set email alerts
|

Standing enhances cognitive control and alters visual search

Abstract: Postural changes and the maintenance of postural stability have been shown to affect many aspects of cognition. Here we examined the extent to which selective visual attention may differ between standing and seated postures in three tasks: the Stroop color-word task, a task-switching paradigm, and visual search. We found reduced Stroop interference, a reduction in switch costs, and slower search rates in the visual search task when participants stood compared to when they sat while performing the tasks. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(98 citation statements)
references
References 63 publications
(67 reference statements)
8
82
7
1
Order By: Relevance
“…As we briefly mentioned in the introduction, an additional study reported by Smith et al (2019) found an influence of posture on the magnitude of the Stroop effect, consistent with the findings of Rosenbaum et al (2017). The obvious question is this: How does Smith et al’s successful replication fit with our present failures to replicate Rosenbaum et al’s findings?…”
Section: Concluding Commentssupporting
confidence: 85%
See 3 more Smart Citations
“…As we briefly mentioned in the introduction, an additional study reported by Smith et al (2019) found an influence of posture on the magnitude of the Stroop effect, consistent with the findings of Rosenbaum et al (2017). The obvious question is this: How does Smith et al’s successful replication fit with our present failures to replicate Rosenbaum et al’s findings?…”
Section: Concluding Commentssupporting
confidence: 85%
“…Experiment 5 was preregistered and conducted at the University of Waterloo following an initial review of a manuscript containing the first four experiments. We also note that while our manuscript was under review, we learned of a recent replication of Rosenbaum et al’s findings by Smith, Davoli, Knapp, and Abrams (2019). We briefly address this replication in the General Discussion.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…While the elaborated experiments related to manipulating various postures by psychotherapy conditions is beyond the scope of this article, as was already mentioned, sitting posture should not be the only body posture option in therapy. For example, Smith, Davoli, Knapp, and Abrams (2019) showed that standing enhances cognitive control and alters visual search, compared to sitting positions.…”
Section: Discussionmentioning
confidence: 99%